2013
DOI: 10.1111/ans.12308
|View full text |Cite
|
Sign up to set email alerts
|

Use of bovine carpal joints as a training model for cruciate ligament repair

Abstract: The use of bovine carpal joints is a cost-effective, safe and easily reproducible model for education on basic anterior cruciate ligament repair skills and technique prior to patient contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Training with human cadaveric models is expensive, and porcine knees, with anatomy similar to the human knee, are inexpensive and readily available [10,11,16,21]. Although arthroscopic training using porcine knees is not a novel concept, studies have not shown that the porcine knee is similar enough to the human cadaveric knee for arthroscopic skills assessment [3,10,21]. This study found that the porcine knee model demonstrated high face validity, because participants attained similar scores on both the human cadaveric and porcine specimens and high reliability with more experienced surgeons achieving higher scores using the porcine model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training with human cadaveric models is expensive, and porcine knees, with anatomy similar to the human knee, are inexpensive and readily available [10,11,16,21]. Although arthroscopic training using porcine knees is not a novel concept, studies have not shown that the porcine knee is similar enough to the human cadaveric knee for arthroscopic skills assessment [3,10,21]. This study found that the porcine knee model demonstrated high face validity, because participants attained similar scores on both the human cadaveric and porcine specimens and high reliability with more experienced surgeons achieving higher scores using the porcine model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cadaveric wet laboratories are often limited to diagnostic arthroscopy to maximize use of specimens for multiple trainees. Computer simulators provide objective feedback and minimize costs associated with repetition, but again their value is limited to basic arthroscopic skills and capital costs are substantial [3,20]. Additionally, trainees using computer simulators forego the haptic feedback that real tissue provides [1], and essential skills such as portal placement and access, managing fluid flow, and the ability to accommodate various techniques and instruments are not incorporated into current simulator models.…”
Section: Introductionmentioning
confidence: 99%
“…noted that the porcine stifles had a wider and smaller medial meniscus when compared with the human meniscus, whereas the lateral meniscus had a fair resemblance to the human meniscus . In addition to the use of the porcine stifle, there have been publications recognizing the practicality of animal models such ovine and bovine stifles as possible modules for arthroscopic training. Another alternative worth considering is the virtual reality arthroscopic simulators that are currently available in several training institutions across the United States …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Alternatives to the use of human cadavers are training with artificial models, 3-dimensional simulators, and animal anatomical models, such as porcine and bovine knee. [4][5][6][7] Simulators and artificial models have the advantage of easy repetition of training, 8,9 but they do not replicate the exact reality of the procedure, such as contact with the texture and resistance offered by human and animal tissue, for example. 7 Several studies have already shown that some anatomical animal models are very close to humans and therefore apply well to the training of open and arthroscopic surgical skills.…”
mentioning
confidence: 99%
“…1,9,10 The bovine model has already been used in several studies and shown itself to be an adequate animal model for arthroscopic training, mainly for arthroscopic triangulation training. 1,6,11 In this article, we describe, step by step, how to set up an arthroscopy laboratory with an anatomical animal model.…”
mentioning
confidence: 99%